INDIVIDUAL COUNSELING WITH CONTRACT ENGINEERING BEHAVIORAL APPROACH TO IMPROVE EMPLOYEE PERFORMANCE IN MR DIY SUN EAST MALL BANYUWANGI (CASE STUDY IN 3 EMPLOYEES) - Bunga Surya Saktiany Putri; Ahmad Sulthoni (International Jurnal of Education Schoolars, 2022)
Guidance Counseling is certainly needed for companies. This is as stated by Handoko (2000) counseling is a discussion of a problem with an employee with the main objective of helping the employee to handle the problem better. One of the services that can be used to improve employee performance is an individual counseling model with a contract technique behavior approach. Individual counseling is a counseling service performed by the counselor to the counselee to alleviate or solve a problem faced by the counselee. The purpose of this study was to determine whether individual counseling behavioral contracting techniques can improve employee performance in MR. DIY Sun East Mall Banyuwangi. This research was conducted to find out and explain that the application of individual counseling with a contract technique behavior approach can be applied to improve employee performance at MR.DIY Sun East Mall Banyuwangi. This research is a type of qualitative case study research. Data collection was done by interview, observation and documentation techniques. The subjects in this study were three people, namely IN, FP, and MWA who were employees of MR.DIY Sun East Mall Banyuwangi who experienced a decrease in performance. The results of this study individual counseling with a contract technique behavior approach succeeded in increasing the performance of IN, FP, and MWA subjects, seen from the results of the self-performance three subjectsThis was also expressed by the assistant branch manager of MR.DIY Sun East Mall Banyuwangi that individual counseling on behavioral contracting techniques can improve employee performance at MR. DIY Sun East Mall Banyuwangi